Design Exploration through Code-Generating DSLs. - SVENSSON, BO JOEL; SHEERAN, MARY; NEWTON, RYAN R. (Communications of the ACM, 2014)
This article demonstrates how high-level embedded DSLs (EDSLs) really can alleviate low-level programming with no contradiction. Topics discussed also include the need for software engineers not to be hesitant when it comes to writing computer programs that generate programs, an EDSL used to generate code that can provide safety guarantees in the generated code if structured properly, deferred-array data as an example of encapsulating code-generation tactics with a nice application programming interface.